The Director's Strategy in Improving the Quality of Drinking Water Services at Perumda Tirta Sinjai Bersatu - Hartati Malkab; Salman Salman; Syahril Syahril; Nurbaya Nurbaya (Universitas Negeri Makassar, 2021)
The need for clean water is increasing over time, but the supply of natural resources in the form of clean and healthy drinking water is starting to decrease in several districts. Clean and healthy water is needed to support all community activities every day because water plays an important role for family needs, irrigation, recreation, and industry. This study aims to find out how the director's strategy in improving the quality of drinking water services at Perumda Tirta Sinjai Bersatu is related to problems, complaints and public complaints. This research includes qualitative research. Data collection techniques used are observation, interviews and documentation. The informants in this study are: Director of Perumda Tirta Sinjai Bersatu, Head of service and billing, Head of subscription relations, Head of Division. Production, Head of Distribution Subdivision and Community as customers of clean water at Perumda Tirta Sinjai Bersatu The data analysis techniques used are data collection, decision making or verification. The results of this study reveal that the Director's strategy in Improving the Quality of Drinking Water Services at Perumda Tirta Sinjai Bersatu is the quality of drinking water services in the form of Direct Evidence, Reliability, responsiveness, assurance, empathy.